Flagellar brake protein YcgR interacts with motor proteins MotA and FliG to regulate the flagellar rotation speed and direction - Han, Qun; Wang, Shao-Feng; Qian, Xin-Xin; Guo, Lu; Shi, Yi-Feng; He, Rui; Yuan, Jun-Hua; Hou, Yan-Jie; Li, De-Feng (Frontiers in Microbiology, 2023)
In E. coli and related species, flagellar brake protein YcgR responds to the elevated intracellular c-di-GMP, decreases the flagellar rotation speed, causes a CCW rotation bias, and regulates bacterial swimming. Boehm et al. suggested that c-di-GMP-activated YcgR directly interacted with the motor protein MotA to curb flagellar motor output. Paul et al. proposed that YcgR disrupted the organization of the FliG C-terminal domain to bias the flagellar rotation. The target proteins are controversial, and the role of motor proteins remains unclear in flagellar rotation speed and direction regulation by YcgR. Here we found that YcgR could interact with both MotA and FliG, and the affinities could be enhanced upon c-di-GMP binding. Furthermore, residue D54 of YcgR-N was needed for FliG binding. The mutation of the FliG binding residue D54 or the MotA binding ones, F117 and E232, restored flagellar rotation speed in wild-type cells and cells lacking chemotaxis response regulator CheY that switched the flagellar rotation direction and decreased the CCW ratio in wild-type cells. We propose that c-di-GMP-activated YcgR regulated the flagellar rotation speed and direction via its interaction with motor proteins MotA and FliG.